An Improved Method of Percutaneous Transhepatic Biliary Drainage Combining Ultrasound-Guided Bile Duct Puncture with Metal Stent Implantation by Fluoroscopic Guidance and Endoscopic Visualization as a One-Step Procedure: A Retrospective Cohort Study - Schmitz, Daniel; Weller, Niels; Doll, Matthias; Weingärtner, Simon; Pelaez, Nuria; Reinmuth, Gabriele; Hetjens, Svetlana; Rudi, Jochen (Journal of Clinical Interventional Radiology ISVIR, 2018)
Aims In recently published comparative studies, it is reported that percutaneous transhepatic biliary drainage (PTBD) is less successful, causes more adverse events, and needs more re-interventions than endoscopic ultrasound-guided biliary drainage (EUS-BD) in patients with malignant extrahepatic bile duct obstruction when endoscopic retrograde cholangiopancreatography (ERCP) fails. Could an improved technique of PTBD produce better results to use this technique for further comparative studies with EUSBD?Methods In our tertiary referral hospital, 116 prospectively documented, and retrospectively analyzed PTBDs with ultrasound guided ductal puncture were performed. In 16 of 30 PTBDs with metal stent implantation in malignant diseases, metal stent was inserted as a one-step procedure by endoscopic luminal guidance in the first session.Results Fifteen of 16 (94%) or 14/16 (88%) of PTBDs with primary metal stent implantation were technically or clinically successful. Mainly the left liver was used as access route for PTBD. Procedure time was 68.1 minutes (25–118), fluoroscopic time: 18.6 minutes (3–46), and patient radiation exposure: 5957 μGy/m2 (471–17,569). In 2/16 (12.5%) patients, adverse events (1 × mild and 1 × moderate grade of severity) were documented. One re-intervention was necessary (0.1/patient) in the observation time of 6 months. The mean overall survival time was 163.2 (7–864) days after PTBD.Conclusions PTBD with ultrasound-guided ductal puncture and primary metal implantation by endoscopic luminal guidance in patients with malignant extrahepatic bile duct obstruction showed good technical and clinical success and low adverse event and reintervention rates in our retrospective cohort study.Clinical Trial Registration:ClinicalTrials.gov ID: NCT03541590.
Keywords: malignant extrahepatic bile duct obstruction; percutaneous transhepatic biliary drainage; ultrasound-guided bile duct puncture